2005
DOI: 10.1021/jp050136p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polymer Micelles of Alkylated Polyethylenimines on Generation of Gold Nanoparticles

Abstract: Mono- and di-alkylated polyethylenimines (PEI-1R, PEI-2R) were synthesized and used as both reductants, by exploiting the functionality of the polyethylenimine's (PEI) amino groups, and stabilizers able to protect nascent gold nanoparticles generated from hydrogen tetrachloroaurate (HAuCl4). From TEM images of the stained polymers, it is clear that the polymer micelles are round and well-structured when formed from PEI-2R, fused and less well-structured when formed from PEI-1R, and totally nonstructured when f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 27 publications
2
74
1
Order By: Relevance
“…According to previous reports [32][33][34][35][36] and our findings presented here, we assumed that the large amount of tertiary amino groups in HBPO-star-PDEAEMA is significant for the preparation of AuNPs. To validate our assumption, we selected some hyperbranched polymers without amino groups as the controls, such as hyperbranched polyglycerol (HPG) and hyperbranched polyester H20, to prepare AuNPs through the same approach.…”
Section: Discussion Of Mechanisms For the Reduction Of Aunpssupporting
confidence: 77%
“…According to previous reports [32][33][34][35][36] and our findings presented here, we assumed that the large amount of tertiary amino groups in HBPO-star-PDEAEMA is significant for the preparation of AuNPs. To validate our assumption, we selected some hyperbranched polymers without amino groups as the controls, such as hyperbranched polyglycerol (HPG) and hyperbranched polyester H20, to prepare AuNPs through the same approach.…”
Section: Discussion Of Mechanisms For the Reduction Of Aunpssupporting
confidence: 77%
“…The primary amine groups in alkyl chains, which is well known to interact with gold ions and the corresponding reduced metal, is expected to exhibit a significant effect on the self-assembly of Au NPs. [25][26][27] William et al reported an incomplete coverage of gold colloids (ranged in 25-120 nm) on indium tin oxide (ITO) surface, i.e., Au NPs were deposited as a discontinuous layer with a large gap among the adjacent particles.…”
Section: 13mentioning
confidence: 99%
“…Both modes of action are governed to a large extent by the pH-dependent degree of cationic charge density. In our previous study, alkylated PEI was used as both a stabilizer and a reducing agent to prepare nanoscale metal particles [8]. It was found the alkyl groups directed the conformation of PEI chains by means of the formation of polymer micelles (soft template) resulting in a system giving effective protection to newly generated gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%